2004
DOI: 10.1136/ard.2003.013201
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination in children with juvenile idiopathic arthritis

Abstract: Objectives: To evaluate the responsiveness of children with juvenile idiopathic arthritis (JIA) to hepatitis B vaccination and to determine the most useful vaccination schedule. Methods: 39 children with JIA were enrolled in the study; all were in remission and negative to serological testing for hepatitis B surface antigen (HbsAg). The control group consisted of 41 healthy children. There were two different vaccination schedules: group I was vaccinated at 0, 1, and 3 months; group II was vaccinated at 0, 1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 11 publications
(8 reference statements)
4
61
1
5
Order By: Relevance
“…The preimmunization rate cannot account for this finding because it was similar to that of the control group. In contrast, previous reports suggest apparently adequate vaccine responses for seasonal influenza 8 and hepatitis 27 in persons with JIA. The inclusion of patients or controls younger than age 9 years 8,27 and 3 years old 8 precludes a definitive conclusion about their findings, as vaccine responses in these 2 age brackets are expected to be much lower than in older children.…”
Section: Discussioncontrasting
confidence: 44%
“…The preimmunization rate cannot account for this finding because it was similar to that of the control group. In contrast, previous reports suggest apparently adequate vaccine responses for seasonal influenza 8 and hepatitis 27 in persons with JIA. The inclusion of patients or controls younger than age 9 years 8,27 and 3 years old 8 precludes a definitive conclusion about their findings, as vaccine responses in these 2 age brackets are expected to be much lower than in older children.…”
Section: Discussioncontrasting
confidence: 44%
“…Both of them showed that the measles, mumps, and rubella booster vaccination was safe in JIA patients, including those who were taking prednisone, MTX, or etanercept (17,18). Studies of effects of inactivated vaccines, including influenza vaccine (19,20), hepatitis B vaccine (21), and meningococcal C vaccine (22), have not shown changes in disease activity or an increase in the occurrence of flares after vaccination in patients with JIA.…”
Section: Discussionmentioning
confidence: 99%
“…(28,29) In a prospective study evaluating the effectiveness of hepatitis B vaccination in children with JIA, no children were found to experience disease flare-up or clinical deterioration after vaccination. (30) In another study, Borte et al reported that there was no worsening of disease activity or any increase in medication use after children with JIA (being treated with anti-inflammatory medications including methotrexate and etanercept) received live-attenuated measles, mumps, and rubella vaccinations. (31) Vitamin D plays an important role in modulating the human immune system.…”
Section: The Environment and Jiamentioning
confidence: 98%